2014
DOI: 10.1007/978-3-319-08001-7_11
|View full text |Cite
|
Sign up to set email alerts
|

Approximability of Connected Factors

Abstract: Finding a d-regular spanning subgraph (or d-factor) of a graph is easy by Tutte's reduction to the matching problem. By the same reduction, it is easy to find a minimal or maximal d-factor of a graph. However, if we require that the d-factor is connected, these problems become NP-hard -finding a minimal connected 2-factor is just the traveling salesman problem (TSP).Given a complete graph with edge weights that satisfy the triangle inequality, we consider the problem of finding a minimal connected d-factor. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Since |Q | > g(n) + 1, we conclude that the number n of vertices of G is greater than (n/g(n) − 2g(n) 2 + 1)(g(n) + 1). Rearranging for n we obtain that n < 2g(n) 4 + 2g(n) 3 + g(n) 2 + g(n) < 6g(n) 4 which contradicts our assumption that n ≥ 6g(n) 4 . Since Q i is a proper refinement of Q i+1 for every i with 1 ≤ i < k and |Q 0 | = 1, we infer that the length of the sequence S is at most g(n) + 1.…”
Section: Lemma 16mentioning
confidence: 73%
See 2 more Smart Citations
“…Since |Q | > g(n) + 1, we conclude that the number n of vertices of G is greater than (n/g(n) − 2g(n) 2 + 1)(g(n) + 1). Rearranging for n we obtain that n < 2g(n) 4 + 2g(n) 3 + g(n) 2 + g(n) < 6g(n) 4 which contradicts our assumption that n ≥ 6g(n) 4 . Since Q i is a proper refinement of Q i+1 for every i with 1 ≤ i < k and |Q 0 | = 1, we infer that the length of the sequence S is at most g(n) + 1.…”
Section: Lemma 16mentioning
confidence: 73%
“…, (H k , Q k ) satisfying properties (M1)-(M4). Recall our assumption that n ≥ 6g(n) 4 . Let (G, f ) be an instance of CONNECTED g-BOUNDED f -FACTOR.…”
Section: Lemma 16mentioning
confidence: 99%
See 1 more Smart Citation
“…We refer this connected regular spanning subgraph as a connected d-factor. Further, recently Cornelissen et al [3] showed that for every 0 < ǫ < 1, for f (v) ≥ n 1−ǫ the connected f -factor problem is NP-Complete.…”
Section: Introductionmentioning
confidence: 99%
“…For the case when f (v) ≥ ⌈ n 2 ⌉ − 1, Cornelissen et al [3] have also shown a simple test for the existence of a connected f -factor. We observe that when f (v) ≥ ⌈n/2⌉ for every v in V , any f -factor of a given graph G is connected and has diameter at most 2.…”
Section: Introductionmentioning
confidence: 99%